Strategi Pengembangan Produksi Pertanian Sektor Hortikultura di Kecamatan Mallusetasi, Kabupaten Barru - Zamzam, Syamsiar; Salim, Ade Putra; Rahim, Abd. (Fakultas Pertanian, Universitas Lampung, 2023)
Mallusetasi District, Barru Regency is trying to improve the agricultural sector in horticultural commodities. Horticultural crops are the mainstay, although it is not yet known and determined which leading horticultural sector will be developed by related parties, in this case the local government. This study aims to analyze the base sector in Mallusetasi District, Barru Regency. The method used in this study is location quotient (LQ) analysis to determine the base sector, dynamic location quotient (DLQ) analysis to determine development potential this year and the next few years and SWOT analysis to determine strategies in developing base sector commodities in Mallusetasi District. The results showed that the horticultural commodity which became the basis sector with superior classification was watermelon. In the development effort through SWOT analysis it was found that the watermelons cultivated in Mallusetasi District were in a position to grow and develop with an aggressive strategy which meant that farmers had to be able to use their power to optimize the use of opportunities in the form of assistance from the government, market access and superior seeds for horticultural commodities.